Papierowa i internetowa. Prasa dla młodzieży - Leska-Dorenda, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
This article is based on the analysis of the results of scientific research on the group of students which was held between March and May 2007. Research was made in the group of children and youth in age of 11-16-students of grammar schools and junior high schools from the rural (Orzechów) and urban (Lodz, Radomsko) area. Summarizing, 768 students (356 from 6 grammar schools, and 402 from 4 junior high schools) took part in the research. The main purpose of the matter was to find the answer to the questions like: Which newspapers are read by the youth? Do they understand the language which is used in those magazines? Which types of text the youth find especially interesting? and How popular internet magazines are among the youth? After collecting and analyzing the results of research, it may be admitted, that youth magazines are very popular form o f the entertainment, and the way of getting knowledge about the world. Over 90 percent of the students buy youth magazines, and almost half of them choose “Bravo”. “Bravo Girl”, “Twist” and “Dziewczyna” are other, less popular papers. The same results prove, that the online magazines do not raise too big interest among youth. Only 10% of the enquired confirmed this type of reading. The research also showed, that the language used in the youth press is not fully understandable for about 1/3 of the enquired. As the reason, the students pointed very often to the overflow of foreign words and incomprehensile vocabulary. Those facts arc undoubtedly striking, taking into consideration the fact, that nowadays the main medium of the expression of the press is the picture, and the newspapers texts are only a comment or a caption under the photography or illustration.